2019
DOI: 10.1002/ca.23410
|View full text |Cite
|
Sign up to set email alerts
|

Defining the anatomy of the neonatal lingual frenulum

Abstract: The lingual frenulum is recognized as having the potential to limit tongue mobility, which may lead to difficulties with breastfeeding in some infants. There is extensive variation between individuals in the appearance of the lingual frenulum but an ambiguous relationship between frenulum appearance and functional limitation. An increasing number of infants are being diagnosed with ankyloglossia, with growing uncertainty regarding what can be considered "normal" lingual frenulum anatomy. In this study, microdi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
50
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 28 publications
2
50
0
6
Order By: Relevance
“…Consistent with the recently described adult and neonatal lingual frenulum anatomy [ 3 , 4 ], we have confirmed that lingual nerve branches are located superficially on the ventral tongue surface, immediately beneath the fascial layer. This emphasizes the vulnerability of these nerve branches during frenotomy surgery, particularly when using any surgical tool that creates thermal energy that can be transmitted into the underlying tissues.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Consistent with the recently described adult and neonatal lingual frenulum anatomy [ 3 , 4 ], we have confirmed that lingual nerve branches are located superficially on the ventral tongue surface, immediately beneath the fascial layer. This emphasizes the vulnerability of these nerve branches during frenotomy surgery, particularly when using any surgical tool that creates thermal energy that can be transmitted into the underlying tissues.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with the recently described adult and neonatal lingual frenulum anatomy [3,4], we have confirmed that lingual nerve branches are located superficially on the ventral tongue surface, immediately beneath the fascial layer.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…But some panelists do not use this term and equate “ankyloglossia” with “anterior ankyloglossia.” When the definition of posterior ankyloglossia was considered, the panel was unable to achieve consensus. 17-22 Some in the group use the term to mean a frenulum that inserts into the posterior portion of the tongue, whereas others think of it as a submucosal tethering of the tongue ( Figure 1B ). Still others feel that it does not exist as an anatomic entity and that the term “posterior ankyloglossia” should be abandoned.…”
Section: Discussionmentioning
confidence: 99%
“…The lingual frenulum is formed from the oral mucosa and connective tissues within 22 weeks of gestation; at the time of its formation, any alteration of embryological processes could cause changes in its anatomical structure [1]. The anatomy of the lingual frenulum is poorly described in textbooks (Sinnatamby and Last [2]; Standring [3]); however, a recent study illustrated how it develops from concurrent muscular and mucous components [4]. Currently, there are no publications providing relevant additional details on the physiological morphology.…”
Section: Introductionmentioning
confidence: 99%